Neonatal anemia due to spontaneous fetomaternal hemorrhage in a term neonate: a case report of an incidental finding and brief review - Hao, Xinxin; Zhang, Yuyu; Gao, Chang; Wang, Qiushi (Frontiers in Pediatrics, 2025)
Fetomaternal hemorrhage (FMH) is a rare perinatal condition characterized by the transplacental transfer of fetal erythrocytes into the maternal circulation. It poses significant risks, including fetal anemia, hydrops fetalis, and maternal alloimmunization, and often remains underdiagnosed due to non-specific clinical presentations and limited diagnostic accessibility. We present a case of a term neonate delivered via cesarean section at 38 weeks’ gestation who exhibited severe anemia and hyperbilirubinemia. Blood group analysis revealed maternal–neonatal Rh incompatibility, while flow cytometry quantified 2.0% fetal erythrocytes in maternal blood. This case underscores the diagnostic value of integrating blood group serology and flow cytometry in FMH confirmation, particularly when standard tests yield equivocal results. A multidisciplinary evaluation of the fetus is the key to early diagnosis and intervention to improve the clinical outcome of perinatal infants.